Perdas de nutrientes e sedimento por erosão e seus efeitos na qualidade da água - Paula, Daniela Tolêdo de [UNESP] (2015)
The preparation of the soil, the presence or absence of vegetation, as well as the proportion of this cover soil can influence the quantities of organic matter and nutrients lost by erosion, hence the preservation of the quality of soil and water. For the above, this study aimed to evaluate nutrient losses by erosion and its effects on water quality in area with cane sugar cultivation us conventional and conservation tillage systems. In experiment 1 the experimental area is located in Guariba - SP, the same soil was classified as red-yellow dystrophic oxisol. The experimental design was completely randomized in a factorial design, 5 treatments with straw cane sugar and 3 repetitions, totaling 15 plots . In the treatments, the straw was manually distributed across the surface of the soil in amounts of 0 ; 0.157 ; 0.35; 0.515 and 0.7 kg, providing roofing 0% (CS0), 25% (CS25), 50% (CS50), 75% (CS75) and 100% (CS100), respectively. The experimental plots were subjected to simulated rain with average intensity of 60 mm h -1 for 65 minutes. It was observed that with increasing soil erosion losses in rill, there is an increase in clay content of the sediment. This fact is directly linked to greater or lesser coverage provided to the soil. There is the need for minimum ground cover of 42 % so there is no enrichment rate (ER) of the sediment eroded by Psed, Pads and clay. The experiment experimental area 2 is located in Pradópolis - SP, in a soil oxisol clayey, which was in time of renewal of cane sugar cultivation. Three tillage systems were used. The experimental plots were subjected to simulated rain with medium intensity around 65 mm h-1 for 75 minutes. In preparing located, as there is greater ground cover, soil loss is much lower than in conventional and reduced. Conventional treatment had higher losses of OM, P, K, Ca and Mg in the sediment. The concentrations of K and P in runoff water can be considered critical for purposes ...